Answer:
Step-by-step explanation:
Volume of the shipping container = Lengt * Breadth * Height
Given
Length = 4x² + 3x
Breadth = x² – 8
Height = 6x +15
Volume of the container = ( 4x² + 3x)( x² - 8)(6x+15)
( 4x² + 3x)( x² - 8) = 4x⁴-32x²+3x³-24x
( 4x² + 3x)( x² - 8) = 4x⁴+3x³-32x²-24x
(4x⁴+3x³-32x²-24x)(6x+15) = 24x⁵+60x⁴+18x⁴+45x³-192x³-480x²-144x²-360x
Collect like terms
( 4x² + 3x)( x² - 8)(6x+15) = 24x⁵+78x⁴-147x³-624x²-360x
Hence the standard form polynomial representing the volume of this shipping container is expressed as V = 24x⁵+78x⁴-147x³-624x²-360x
That's Roman numerals but it is 1636 not as Roman numerals hope I helped
X intercepts- (2,0) and (-2,0)
y intercept- (0,-8)
Answer:
7
Step-by-step explanation:
13t = 82.3 + 8.7
13t = 91
t = 91/13 = 7
------------------------------------------------------------------------------------------
Equation
------------------------------------------------------------------------------------------
y = -3x - 9
------------------------------------------------------------------------------------------
Option 1
------------------------------------------------------------------------------------------
If I substitute x = -9, I should get y = 0
When x = -9
y = -3 (-9) - 9
= 18 (I did not get 0, wrong)
------------------------------------------------------------------------------------------
Option 2
------------------------------------------------------------------------------------------
If I substitute x = -3, I should get y = 0
y = -3(-3) - 9
y = 9 - 9
y = 0 (Yes, I got 0, correct)
------------------------------------------------------------------------------------------
Option 3
------------------------------------------------------------------------------------------
If I substitute x = 0, I should get y = -3
y = -3 (0) - 9
y = 0 - 9
y = -9 (I did not get -3, wrong)
------------------------------------------------------------------------------------------
Option 4
------------------------------------------------------------------------------------------
If I substitute x = 0, I should get y = -9
y = -3 (0) - 9
y = 0 - 9
y = -9 (Yes, I got -9, correct)
------------------------------------------------------------------------------------------
Answer: (-3, 0) and (0, 9) are ordered pairs of the equation (Answer B, D)
------------------------------------------------------------------------------------------